Evaluation of risk factors for morbidity and mortality in children aged 1 month- 6 years presenting with lower respiratory tract infection to a referral hospital - Tewary, Shambhavi; De, Sanjukta; Khawash, Papiya (International Journal of Contemporary Pediatrics, 2023)
Background: Acute lower respiratory tract infection (LRTI) is the single largest cause of death in children in most developing countries. It can be prevented by simple interventions and treated with low-cost medication and care. Hence we undertook this study with the aim to assess the severity of LRTI in children using the respiratory index of severity in children (RISC) scoring system and to evaluate the prognosis of these children using this scoring model and to evaluate which are the risk factors that consistently predict mortality and morbidity in LRTI in young children. Methods: It was a prospective observational study which included 104 children aged 1 month-6 years presenting with LRTI. Data was collected using a pre-coded proforma and analysed using R 2.6.2 (2008-02-08) and Microsoft excel. Results: The risk factors for adverse outcome in children with LRTI were age <6 months, refusal of feeds, hypoxemia (SpO2 <90% in room air), and positive chest X-ray findings for prolonged hospitalization, age <6 months for need for assisted ventilation. 62.79% of children with a RISC score of ≤0, were managed as outpatients and all children with a RISC score of ≥3 required hospitalization, of which, 88.89% required prolonged hospitalization and 19.4% required ventilation. Conclusions: A high RISC score (≥3) can determine poor outcome in children with LRTI with high specificity and sensitivity. This study may be used to limit hospital referrals to those most in need, especially in resource limited regions, thereby improving the number of children receiving appropriate treatment.